Impact Of Earthing Deviation On Surge Protection Devices - Lee, Yao Dong (2021)
Power surge is a phenomenon where a sudden rush of energy is being introduced into a system. Among many surges, lightning is the more common one that is familiar in the eyes of the public. Surges are destructive in nature and often times cause unnecessary damages to equipment or even human lives. A surge protection device (SPD) can be used as a protective equipment to prevent such unfortunate events to occur. In this research, the different sources of which surges originated from is explored while studies are performed to investigate how earth impedance can affect the performance of the SPD to react towards a surge event. In this project, a surge generator is modelled and is able to generate a desired surge waveform that is in accordance to the IEEE 6100-4-5 standard. Applying the surge onto an electrical network, it was found that connecting a high earth resistance is better for overvoltage protection when using a MOV surge arrestor SPD to protect the load. The voltage fall time and clamping voltage of the MOV shows better performance when connected to a higher earth resistance. However, the MOV shows it reacts more quickly towards a surge when it is connected to a lower earth resistance due to the higher peak voltage being reflected across the MOV. These results both are considered valid as it holds true to the potential divider hypothesis that is mentioned in the report.